Optimizing digital implant impressions: Evaluating the significance of scan body image deficiency and alignment under varied scan body exposures - Petchmedyai P. (2023)
In implant dentistry, the advent of intraoral scanning technology has revolutionized traditional clinical processes by streamlining procedures and ensuring predictable treatment outcomes. However, achieving accurate virtual implant positions using intraoral scanners and scan bodies can be influenced by various clinical and laboratory factors. This study aims to investigate the impact of scan body image capture deficiency and scan body alignment methods in computer-aided design (CAD) software on the accuracy of virtual implant positions, particularly in different implant depths. Three stereolithographic half-arch implant models with different implant depths were prepared, representing three scenarios of scan body exposure: full exposed scan body, 2/3 exposed scan body, and 1/3 exposed scan body. The scan body image capture deficiency and alignment methods were simulated using CAD software. The deviation of virtual implant positions obtained from different scenarios were evaluated using 3D analysis software. The highest angular and linear deviation (0.237±0.059 degrees, 0.084±0.068 mm) were found in the 1/4 upper and lower part scan body deficiency using the 1-point alignment method in the 1/3 exposed scan body. Two-way ANOVA analysis revealed significant effects of scan deficiency on virtual implant position deviations across all scan body exposures, except for the linear deviation when the scan body was exposed 2/3 of its length. Furthermore, scan deficiencies in the 1/4 upper and lower parts of the scan body significantly affected implant angular deviation regardless of scan body exposure, while implant linear deviation was specifically affected when the scan body was exposed to only 1/3 of its total length. Deficiencies in scan body acquisition, particularly in deep soft tissue situations, can lead to deviations in both angular and linear positioning of virtual implants. Employing appropriate scan body alignment methods such as a 3-point alignment approach demonstrates better accuracy compared to a 1-point alignment.